Nurses' Experiences of Critical Care in the COVID-19 Intensive Care Unit - Alirez Mirjalili; Samaneh Mirzaei; Khadijeh Nasiriani (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Background: The intensive care unit is one of the essential and vital departments of hospitals that accommodate patients in critical condition. Intensive care nurses play an important role in the evaluation, treatment, and management of these patients. The outbreak of the COVID-19 (Coronavirus disease ) pandemic, followed by severe respiratory involvement, highlighted the importance of nurses' performance in the intensive care unit. The aim of this study was to explain the nurses' experiences of nursing care in the COVID-19 intensive care unit.Methods: This study was qualitative content analysis. Participants were 12 nurses who were selected based on purposive sampling. Data collected by semi and unstructured interview. Data analysis was performed based on Graneheim and Lundman (2004) at three-phase. Research trustworthiness was confirmed by four criteria of credibility, transferability, dependability, and conformability.Results: In this study, a total of 1311 meaning units were extracted; after condensation and abstraction, 257 codes were obtained, which were extracted into 32 primary subcategories, eight secondary subcategories, and two themes. The first theme was nursing care inhibitors in the COVID-19  (Coronavirus disease) Intensive Care Unit included five categories: "Problems with personal protective equipment, lack of care supplies, Insufficient preparation  of intensive care nurses, burnout of nurses, and care burden." The second theme was the strengths of nursing care in the intensive care unit in the COVID-19 included three categories: "Acquiring new knowledge and experience of intensive care, upgrading and developing the intensive care system and improving the image of nursing in the community."Conclusion: The COVID-19 pandemic was associated with challenges and problems for nursing and nursing care, the identification of which can help prepare for future crises. Also, due to its positive achievements for nursing, it can be used to improve the position of nursing and its care.